نیشتەجێبوونى عەرەب لە ناوچەى کوردە فەیلیەکاندا - محەمەد, خەلیل ئیسماعیل (Sulaimani Journal for Humanities, 2001)
The ultimate goal of this study is the disclosure of the plans of arabization which have been undertaken by the Iraqi state since its establishment in 1921 till now in Iraqi Kurdistan Region, and the results of such plans. The study coprises the following axes: 1- The axes of the east of Baghdad (The homeland of AL -Kurd-al-faylin). 2- The axis of AL -jazira(Mosul). 3- The axis of Kirkuk. The study begins with an introduction about the start of Arabic settlement in Iraq, especially after the waves of the Arabic tribes during the Islamic conquests which had deep influences in changing the national character of Iraq. Then the study examines the Arabic waves which progressed across Tigris and Euphrates towards Iraq Kurdistan Region. The study has elaborately concentrated on the first axis related to AL-Kurd-al-faylin especially their homeland and their geographical distribution in Iraq, and the sketching of the Iraq-Iranian boundaries along with its political and national results. The study has, among other attempts of Arabization, disclosed the names and the settlement periods of the Arabic tribes settled in the districts of AL-Kurd-al-Faylin. The study also deals the policy of Iraqi state in encouraging this type of settlement by deporting the original citizens to the other side of the boundaries under the pretext that they were Iranians by nationality. The study reaches the following conclusions: The region of AL- Kurd-al-Faylin have been subjected for many centuries, to continuous innovations by the moving Arabic tribes which settled in the fertile Lands near the valise of the main rivers in the Region. The sketching of the boundaries between Iraq and Iran caused the unity of AL - Kurd -al-faylin to split on one hand, and encouraged the deporting operation tackled by the Iraqi state, on the other. The encouragement of the settlement of the Arabic tribes, especially in the governorates of (Diala) and (Wasit), and the continuation of the policy of deportation all caused a change in ethnic formation of the citizens of the region, which is itself a real danger to the future of all Kurds in general and to their vital issue in particular. Finally, the study calls all responsible in the region and all human rights organizations to prevent such a case and to act in the direction of bringing back the already deportees to their native country and also to compensate them for the injustice and privation they suffered alones last decades.